2020
DOI: 10.29207/resti.v4i1.1517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Data Scaling on the Performance of the Machine Learning Algorithm for Plant Identification

Abstract: Data scaling has an important role in preprocessing data that has an impact on the performance of machine learning algorithms. This study aims to analyze the effect of min-max normalization techniques and standardization (zero-mean normalization) on the performance of machine learning algorithms. The stages carried out in this study included data normalization on the data of leaf venation features. The results of the normalized dataset, then tested to four machine learning algorithms include KNN, Naïve Bayesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
0
24
0
6
Order By: Relevance
“…While there are several data scaling techniques available, one of the main challenges associated with ML is to choose the appropriate scaling method. Many studies bolster the effect of data scaling techniques on different ML algorithms [31,32]. Shahriyari et al (2019) showed that the performance of normalization has a significant effect on different ML approaches [32].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are several data scaling techniques available, one of the main challenges associated with ML is to choose the appropriate scaling method. Many studies bolster the effect of data scaling techniques on different ML algorithms [31,32]. Shahriyari et al (2019) showed that the performance of normalization has a significant effect on different ML approaches [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study conducted by Ambarwari et al (2020) showed that data scaling techniques such as MinMax normalization and standardization have also significant effects on data analysis [31]. The study was carried out using ML algorithms such as KNN, Naïve Bayesian, ANN, and SVM with RBF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of the works in the literature that have investigated the effect of the min-max data normalization reported a positive impact of the min-max normalization on the adopted ML techniques in their studies (Dadzie and Kwakye, 2021;Shahriyari, 2017), while some other studies determined that its usefulness varies from good to bad depending on the nature of the datasets and the ML model (Ambarwari, Adrian, and Herdiyeni, 2020) (Ahsan, et al, 2021). On the other hand, very limited studies concluded the degradation of the ML model accuracy with the present of min-max normalization.…”
Section: Related Workmentioning
confidence: 99%
“…Many research works showed that SVM has more sensitive responds than ANN and E-KNN toward the normalization techniques. Results in many SVM-based works showed the usefulness of using min-max normalization with SVM (Dadzie and Kwakye, 2021;Shahriyari, 2017;Ambarwari, Adrian, and Herdiyeni, 2020). Despite that, there are still some studies proved that normalization has no effect or has very little effect on the accuracy rate of the SVM-based models (Singh, et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation